SPIRITUAL VALUES OF THE PHILOSOPHY OF COSMISM AND EDUCATIONAL SPACE IN THE INFORMATION SOCIETY - Сухова, Н. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
Introduction. A globalized world motivates a modern person to seek actively new forms and ways for the further survival on Earth. Ide-als and values of the philosophy of cosmism are increasingly becoming very topical today. Aim and tasks: The author considers the influence of the philosophy of cosmism on values of educational space of the Information society. Studying the problem is carried out within the framework of philosophical discourse between physicists, philosophers, psychologists, educators, neurolinguists, and others. Research methods: It is used a comparative approach which helps to compare fruitfully the data obtained from researches of educa-tors, psychologists and philosophers with regard to the specifics of using the Cosmism values in the era of global changes at the plane-tary scale. Results. Modern consumer-utilitarian attitude towards nature, to state and its various institutions has caused many problems, without the solution of which humanity will destruct itself as a biological species. Economy centrism is the main feature of the global world, whereas the philosophy of Russian cosmism is a man-centrism studying. Representatives of various branches of knowledge, who were being influenced by a Cosmism, are analyzed. The significant role of higher education in the educational sphere is underlined. Discussion. The scientific community unanimously insists on revising the value orientations, which are still aimed at indicators of eco-nomic efficiency and depreciation of human life. The values and ideals of the Cosmism should be carefully learned by modern re-searchers, since modern Cosmism differs significantly from the classical one. The globalization, predicted by K. Tsiolkovsky, has been evolving along a different scenario. Therefore, the influence of the Cosmist’s philosophy values on the educational sphere of the infor-mation society is not sufficiently studied. Conclusion. In the process of an economically-centred society, the ideals of Cosmism became declarative slogans exclusively for the human educational sphere. Anthropological catastrophe is directly related to the deformation of the educational sphere, when a part of humanitarian subjects in education is constantly reduced, or meaninglessly unified, ignoring the principle of the fundamental nature of education. We hope, through the human experience a new type of thinking would be established and the awareness of the inevitable responsibility for their choice would also come soon.